Bridging the medieval-modern divide: medieval themes in the world of the Reformation - Muldoon, James (Catholic christendom, 1300 - 1700, 2013)
Medieval roots of the modern image of Islam: fact and fiction / Meriem Pages -- Toleration in medieval Europe: theoretical principles and historical lessons / Cary Nederman -- "Atheism" in medieval travel writings / Margaret Kim -- Purgatory and modernity / George Dameron -- The revival of medieval biblical exegesis in the early modern world: the example of Carolingian biblical commentaries / Burton Van Name Edwards -- Continuity or radical change? Care of the poor, medieval and early modern / Jeannine Olson -- Rights, property, and the creation of international law / James Muldoon -- "A divine precept of fraternal union": The maxim quod omnes tangit in Anglo-American thought to the ratification of the Constitution / Bruce Braisington